MicroRNA-155 Participates in the Expression of LSD1 and Proinflammatory Cytokines in Rheumatoid Synovial Cells - Ziliang Yu; Hao Liu; Jianbo Fan; Feihu Chen; Wei Liu (Hindawi Limited, 2020)
MicroRNA-155 (miRNA-155) is abundant in fibroblast-like synoviocytes (FLS) in rheumatoid arthritis (RA). Lysine-specific demethylase 1 (LSD1) has been found that it can ameliorate the severity of RA. Tumor necrosis factor-alpha, interleukin-1 beta, and interleukin-6 are key proinflammatory cytokines implicated in the pathogenesis of RA. In our study, we investigated whether miRNA-155 participates in the expression of LSD1 and proinflammatory cytokines in rheumatoid synovial cells. First of all, flow cytometry and cell counting kit-8 analysis were employed to explore the apoptosis and proliferation of FLS, respectively. Subsequently, reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was applied to probe into the level of miRNA-155 in FLS when stimulated by miRNA-155 molecules. Moreover, RT-qPCR was used to explore the relative LSD1 miRNA expression in FLS when stimulated by miRNA-155 molecules, and Western blot and immunofluorescence assay were applied to probe into the expression level of LSD1. Finally, enzyme-linked immunosorbent assay was employed to analyze the secreting level of proinflammatory cytokines in FLS when stimulated by miRNA-155 molecules. RA-FLS showed a higher apoptosis rate than normal FLS. The cell proliferation of both HFLS and MH7A cells was promoted by miRNA-155 upregulation. Meanwhile, the expression of LSD1 and proinflammatory cytokines in the FLS of RA was also changed by miRNA-155 regulation. In conclusion, miRNA-155 participates in the expression of LSD1 and proinflammatory cytokines in rheumatoid synovial cells. These findings imply a potential function and interaction of miRNA-155 and LSD1.